PSIKOLOGI ISLAM: Sejarah, Tokoh, dan Masa Depan - Yandi Hafizallah; Sadam Husin (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This paper aims to explain and analyze Islamic psychology based on the historical approach and analyze the flow of western psychology using the Islamic psychology approach. This study refers to the history of Islamic psychology from the 19th century to the modern age today, and also how the development of the psychology of religion, especially Islam in Indonesia. Islamic Psychology itself has three concepts based on the Qur'an, among others: 1) The dimension of jismiah which means human physical organs, this aspect has two properties, the first is concrete and the second is abstract, 2) the Nafsiyah dimension which means mind, feeling, will and freedom. This aspect is spiritual, transcendent, sacred, free, independent and inclined towards goodness. This dimension is divided into three aspects, namely: a) an-nafs b) al-Aql c) Qalb. 3) Ruhaniah dimension which means the psychological aspect of man, this aspect has two things namely the origin and the existence. The three aspects above are expected to be able to be used to develop Islamic psychology and determine the direction as well as challenges for scientists in the future.